Leveraging AI-enabled mobile learning platforms to enhance the effectiveness of English teaching in universities - Shanshan Guo; Huzaina Binti Abdul Halim; Mohd Rashid Bin Mohd Saad (Scientific Reports)
Abstract The AI era has ushered in a new wave of opportunities for enhancing classroom education, particularly in the realm of higher education. This study investigates the integration of AI and mobile learning technologies to promote innovation and reform in education. It explores how AI-driven platforms, using soft computing networks, can improve students’ critical thinking skills and foster deeper engagement with academic subjects. The research also examines the deployment techniques and procedures for incorporating mobile learning technologies into higher education settings. A comparison experiment is conducted to assess the effectiveness of the AI-driven system against traditional learning methods, revealing that AI-based learning enhances student motivation and practical skills. The study highlights the broader implications of AI in education, including its potential to facilitate global collaboration, enhance educational equity, and address the evolving needs of digitally connected learners. Finally, the paper suggests directions for future research, including the application of AI across various academic disciplines and the exploration of ethical considerations in AI-driven education.